An Analysis of the 4A Concept (Attraction, Amenity, Accessibility, and Ancillary) at the Mangrove Sungai Bersejarah Ecotourism Destination - Fahmi Muhammad; Firdaus Yusrizal; Ahmad Nawawi; Riau Nurita; Nur Arini Yulia (Politeknik Sahid, 2026)
This research aims to analyze the actual conditions of the 4A aspects (Attraction, Amenity, Accessibility, and Ancillary) at the Mangrove Sungai Bersejarah Ecotourism Destination (MSB) in Kayu Ara Permai Village, Sungai Apit District, Siak Regency. The research uses a qualitative approach with a case study design. Data was collected through in-depth interviews with MSB administrator, communities, government officials, academics, and tourists, direct observation in the field, and documentation studies. Data analysis was conducted using descriptive qualitative methods, grouping findings based on each 4A aspects. The results showed that the attraction aspect was the main strength of the destination, characterized by the integrity of the mangrove ecosystem, the beauty of the coastal landscape, the educational and historical value inherent in the area. However, tourist attractions were still dominated by passive natural potential and had not been packaged thematically. The amenity aspect has provided basic facilities such as track path, toilets, prayer rooms, and meeting rooms, but their quality, safety, and cleanliness are still limited. The accessibility aspect shows that the destination can be reached by land route, but it is still constrained by a lack of signposts, limited public transportation, and internal access that is not yet inclusive. Meanwhile, the ancillary aspect is supported by community initiatives through conservation groups, but it is not yet supported by formal tourism institutions, adequate managerial capacity, and cross-sector policy synergy. Overall, the integration of the 4A aspects still needs to be strengthened to support the development of sustainable mangrove ecotourism.